Measurement and Testing of Inequality from Time Series of Deciles with an Application to U.S. Wages - Harvey, Andrew; Bernstein, Jared (The Review of Economics and Statistics, 2003)
This article uses unobserved-components time series models to capture the underlying trends in the quarterly deciles of U.S. hourly wages. Tests of stability and divergence are developed as a means of assessing changes in inequality. The decrease in the wage gender gap is examined, and the impact of changes in the minimum wage is assessed.